West of Memphis - Berg, Amy; Alberti, Maryse; Killeen, Ronan (Sony Pictures, 2013)
In 1994, teenagers Damian Echols, Jason Baldwin and Jessie Misskelley were tried and convicted for the murder of three eight-year-old boys in West Memphis, Arkansas. The murders were gruesomely linked to Satanism and the trial was sensationalized across the news as the story was scrutinized right up until Baldwin and Misskelley were sentenced to life, and Echols was sentenced to death. In the 18 years since they were locked in prison, a growing number of people began to have doubts about the evidence gathered by West Memphis police and support began to grow, as many questioned whether the actual killer was still on the loose. Amy Berg's "West of Memphis" is an all-encompassing analysis of police and court inequality, chronicling the journey of supporters that dedicated their time to fight for justice, leading to the eventual release of the men dubbed "the West Memphis Three". [www.exclaim.ca]
Keywords: DVD-Video